Introduction to data science : data analysis and prediction algorithms with R - Irizarry, Rafael A. (CRC Press, Taylor & Francis Group, 2020)
"The book begins by going over the basics of R and the tidyverse. You learn R throughout the book, but in the first part we go over the building blocks needed to keep learning during the rest of the book"- Resumé vydavatel
Keywords: statistika; algoritmizace; vizualizace informací; R (programovací jazyk); statistics; algorithmization; information visualization; R (programming language); učebnice vysokých škol; textbooks (higher)